2007
DOI: 10.1590/s0034-89102007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Captura de culicídeos em área urbana: avaliação do método das caixas de repouso

Abstract: OBJETIVO: Avaliar a ocorrência de população adulta de culicídeos em área urbana e medir a sensibilidade do método de coleta em caixa de repouso MÉTODOS: Foram coletados mosquitos entre 1999 e 2000, em duas cidades do Estado de São Paulo: Ocauçu e Uchoa. Em cada uma delas, sortearam-se 15 quadras, e em cada quadra um domicílio, onde foram instaladas duas caixas de repouso, no intra e no peridomicílio. Realizaram-se coletas mensais por domicílio, durante 13 meses, utilizando aspiradores manuais no intra e perido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…They are important factors for the maintenance of this mosquito in homes. 3 Bonfi m et al 9 report that precarious basic sanitation systems, such as those found in the neighborhood studied, favor an increase in the number of breeding sites and consequently contribute to high population densities of C. quinquefasciatus.…”
Section: Discussionmentioning
confidence: 90%
“…They are important factors for the maintenance of this mosquito in homes. 3 Bonfi m et al 9 report that precarious basic sanitation systems, such as those found in the neighborhood studied, favor an increase in the number of breeding sites and consequently contribute to high population densities of C. quinquefasciatus.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, these adults can oviposit and shelter themselves there (endophily). Several authors have reported this behaviour, which favours intradomiciliary premises for breeding grounds and the deposit of eggs [ 9 , 28 , 29 ]. Our data confirm previous findings on the bio-ecology of this species in an urban area, supporting the use of teams for the surveillance and control of adult forms of the vector in houses.…”
Section: Discussionmentioning
confidence: 99%
“…Barata et al [ 36 ] captured 0.4 females/house in São José do Rio Preto (SP), Brazil. Barata et al , [ 9 ] in the municipality of Ocauçu and Uchoa (SP), captured 0.4 and 0.7 females/house, respectively, with resting boxes. Fávaro et al [ 28 ], in studying density in two areas of Mirassol (SP), Brazil, reported that the mean number of females captured with aspirators ranged from 0.05 to 0.46 and from 0.08 to 0.62 at areas A and B, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, their sensitivity is likely to be site-specific and strongly influenced by house design. Resting boxes were found to be highly selective in sampling specific mosquito species in coastal areas of the United States of America [49], but have also shown potential for monitoring Culex quinquefasciatus and Aedes aegypti in urban Brazil [50]. …”
Section: Introductionmentioning
confidence: 99%